Evaluation of the L-CLONE Legionella pneumophila Serogroup 1 Urine Antigen Latex Test. - Leland, D S (1991)
The purpose of this study was to evaluate the L-CLONE Legionella pneumophila Serogroup 1 Urine Antigen Latex Test (Access Medical Systems, Inc., Branford, Conn.) for detection of Legionella antigen in urine. A total of 481 frozen urine samples previously tested by an in-house solid-phase radioimmunoassay (RIA) was thawed and retested by using L-CLONE. Included in this sample were 140 RIA-positive samples from culture-positive or serologically confirmed cases of legionellosis and 341 RIA-negative samples from patients with non-Legionella respiratory disease or bacteriuria. The original RIA test result was accepted as the true value. L-CLONE correctly identified 76 of 140 (54%) known positive samples. False-negative results could not be attributed to a low Legionella antigen concentration or to a Legionella antigen subgroup. L-CLONE correctly identified 252 of 341 (74%) known negative samples. False-positive results were experienced in all groups of negative samples, regardless of the patients' underlying diseases. A total of 141 fresh urine samples was tested; all were Legionella antigen negative by RIA. L-CLONE provided 86% specificity. The sensitivity of the L-CLONE in testing fresh urine samples could not be evaluated because of the lack of Legionella antigen RIA-positive samples.